EKSOTIKA INSKRIPSI ARAB PADA KERIS TANGGUH KAMARDIKAN - Abdul Jawat Nur (Arabic Literature Department, 2020)
This study discusses the exotic Arabic inscriptions on kamardikan kris based on sociopragmatic studies. This research is interesting to do because not all kamardikan kris found Arabic inscriptions. The existence of Arabic inscriptions on the kamardikan kris is interesting to study from the type of Arabic script and also the intention of the owners to collect the kris. The method used in this study is the method of providing data, the method of analyzing data, and the method of presenting the results of data analysis. Based on an analysis of the types of Arabic script on the kamardikan keris it is concluded that Arabic writings on the kamardikan kris use one type of writing, namely naskhī writing and diwānī writing and some use a combination of several types of writing, namely (a) naskhi and diwāni writing, (b) Naskhī, Țugrā, and Śuluśi writing, (c) Naskhī, Țugrā, and Raihanī writing, (d) naskhī and Diwanī Jalī writing, and (e) writing the tattoo. Based on sociopragmatic studies, the Arabic inscriptions on the kamardikan kris have (a) aesthetic, (b) symbolic, (c) safety, and (d) success functions.